2010
DOI: 10.3174/ajnr.a2078
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT Angiographic Plaque Morphologic Characteristics in Addition to Stenosis in Predicting the Symptomatic Side in Carotid Artery Disease

Abstract: BACKGROUND AND PURPOSE:Atherosclerotic disease of the carotid artery is an important cause of ischemic stroke. We evaluated carotid plaque morphologic features by using CTA in addition to stenosis in the setting of symptomatic hemispheric TIA/stroke to identify factors that may predict plaque activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…A more interesting approach would be to use the calcified plaque volume as a marker for ischemic symptoms. 15 A recent study 17 suggested that extensive calcification is more commonly associated with the asymptomatic side. However, Nandalur et al 18 have shown that the ratio of calcified plaque volume and total plaque volume is significantly inversely associated with the occurrence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A more interesting approach would be to use the calcified plaque volume as a marker for ischemic symptoms. 15 A recent study 17 suggested that extensive calcification is more commonly associated with the asymptomatic side. However, Nandalur et al 18 have shown that the ratio of calcified plaque volume and total plaque volume is significantly inversely associated with the occurrence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, our work supports data from previous CTA studies of carotid plaque, suggesting that extensive calcification may afford a protective effect, possibly by preventing adhesion and subsequent aggregation of platelet-rich thrombi, although this claim requires further histopathologic confirmation. 24 An additional strength of maximum soft plaque thickness measurements is that such data are readily acquired from standard axial source images in CTA, with a highly reproducible simple linear measurement. Wintermark et al, 25 for example, demonstrated in a cross-sectional analysis from CTA data that certain carotid wall characteristics were significantly associated with stroke, including wall volume, fibrous cap thickness, and number and location of lipid clusters on source images.…”
Section: Discussionmentioning
confidence: 99%
“…From the axial source images, image post-processing can be performed to produce an angiographic display, identifying plaque calcium, luminal surface ulceration (Saba et al, 2007; U-King-Im et al, 2010) and intraluminal thrombus (Eesa et al, 2010). However, limitations of CT and CT angiography (CTA) include exposure to ionizing radiation in addition to artefacts induced by calcification and implanted metallic devices.…”
Section: Imaging Modalities For Assessing Focal Carotid Plaque Hemorrmentioning
confidence: 99%